Prompting Clinicians: A Systematic Review of Preventive Care Reminders - Dexheimer, Judith W (American Medical Informatics Association, 2005)
Prompting clinicians to offer preventive care procedures has been shown to increase the use of these procedures. This study is an update of a systematic review examining the effect of reminder systems on offers of preventive care to patients. Of 1,404 eligible studies, 23 were included. The studies were evaluated according to their intervention type and use of computerized methods. We found that although computerized reminder systems have become more common, paper-based reminders were the most effective reminder strategy.